2020
DOI: 10.1109/tits.2019.2942096
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Consistent Depth Prediction With Flow-Guided Memory Units

Abstract: Predicting depth from a monocular video sequence is an important task for autonomous driving. Although it has advanced considerably in the past few years, recent methods based on convolutional neural networks (CNNs) discard temporal coherence in the video sequence and estimate depth independently for each frame, which often leads to undesired inconsistent results over time. To address this problem, we propose to memorize temporal consistency in the video sequence, and leverage it for the task of depth predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 60 publications
(145 reference statements)
0
25
0
Order By: Relevance
“…The contributions of this study are summarized as follows: (1) We introduce a novel CNN architecture for achieving running efficient and accurate depth estimation from a single image; (2) We design a hybrid loss function; (3) We evaluate the proposed method on a dataset consisting of small sized synthetic images. In particular, we show that the size of the filters used in the input layer of CNNs has an influence on the performance of MDE when small sized images are processed; (4) We use Pareto Optimality to compare the error and running time over different methods, which has not been exploited in depth estimation; and (5) We demonstrate that the proposed method not only generates comparable accuracy to the state-of-the-art methods which use either extremely deep and complex architecture or post-processing but also runs much faster on a single less powerful GPU.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The contributions of this study are summarized as follows: (1) We introduce a novel CNN architecture for achieving running efficient and accurate depth estimation from a single image; (2) We design a hybrid loss function; (3) We evaluate the proposed method on a dataset consisting of small sized synthetic images. In particular, we show that the size of the filters used in the input layer of CNNs has an influence on the performance of MDE when small sized images are processed; (4) We use Pareto Optimality to compare the error and running time over different methods, which has not been exploited in depth estimation; and (5) We demonstrate that the proposed method not only generates comparable accuracy to the state-of-the-art methods which use either extremely deep and complex architecture or post-processing but also runs much faster on a single less powerful GPU.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…Autonomous vehicles have been extensively used in many applications, such as aerial surveillance, search and rescue. In order to safely operate in cluttered and unpredictable environments, these vehicles require a strong awareness of their operational surroundings, in particular, the ability to detect and avoid stationary or mobile obstacles [1], [2]. Depth estimation provides a geometry-independent paradigm in order to detect free, navigable space with the minimum safe distance.…”
Section: Introductionmentioning
confidence: 99%
“…With advances in deep networks, Eigen et al [2] showed that monocular depth estimation with deep neural network yields significant gains in accuracy and speed compared to the traditional attempts with handcrafted features. Starting with the work of Eigen et al [2], many learning-based methods [1,3,4,5,6,7,8,9,10,11] have been studied and showed high accuracy in overall depth evaluation metrics. However, they still produce noisy and temporally flickering depth maps because they perform depth estimation on each frame independently or do not use temporal information correctly.…”
Section: Introductionmentioning
confidence: 99%
“…Several video-based depth estimation methods have been studied, and the core idea behind these methods is to utilize temporal information. Temporal consistency can be explicitly constrained [1,7,8,9,12,13] or implicitly constrained using the recurrent neural networks [7,10,11]. Eom et al [7] proposed the recurrent model with a flow-guided memory unit for consistent depth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation